Prognostic Significance of the Modified Glasgow Prognostic Score in Patients With Pancreatic Cancer: A Meta-Analysis - Wen Fu; Kun Wang; Shan Yan; Xie Wang; Bo Tang; Jiang Chang; Ran Wang; Tao Wu (SAGE Publishing, 2020)
Background: The prognostic value of the modified Glasgow prognostic score (mGPS) in patients with pancreatic cancer is controversial, based on previous studies. Therefore, this meta-analysis aimed to explore the relationship between mGPS and prognosis in pancreatic cancer. Methods: The databases PubMed, Web of Science, Embase, and the Cochrane Library were searched to identify eligible studies. Hazard ratios (HRs) and 95% confidence intervals (CIs) were used to estimate the associations between mGPS score and survival outcomes. Results: A total of 26 studies with 5198 patients were included in this meta-analysis. In a pooled analysis, elevated mGPS predicted poorer overall survival (OS; HR = 1.98, 95% CI, 1.65-2.37, P < .001). In addition, elevated mGPS was also significantly associated with worse progression-free survival (PFS), disease-free survival (DFS), and cancer-specific survival (CSS; HR = 1.95, 95% CI, 1.36-2.80, P < .001). Subgroup analyses confirmed a significant association between mGPS and survival outcomes. Conclusions: Our meta-analysis demonstrated that high mGPS was correlated to worse OS, PFS, DFS, and CSS in patients with pancreatic cancer. Therefore, mGPS could be employed as an effective prognostic factor for pancreatic cancer in clinical practice.